The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21276/ijcmr.2018.5.5.20
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Ectopic Pregnancy, the Challenges for the Obstetrician: Single Center Prospective Study

Abstract: Introduction: Ruptured ectopic pregnancy is a life threatening obstetrical emergency and presents in various ways. The aim was to evaluate predisposing factors associated with development of ectopic pregnancy in current scenario and evaluation done for association between ectopic pregnancy and constellation of signs/ symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
4
3
1
Order By: Relevance
“…The incidence of ectopic pregnancy was 0.86% which was similar to a study by Yadav A et al 13 (0.89%) whereas slightly higher incidence was seen in other studies 1.3%, 14 1.4%, 15 1.8% 16 and 1.9%. 17 The majority of ectopic pregnancy cases occurred in 30 to 34 years age group (28.4%) which was similar to a study by Kaveri et al, 16 (31 to 35 years). However, other studies [17][18][19] found more of these cases in 20 to 30 years age group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The incidence of ectopic pregnancy was 0.86% which was similar to a study by Yadav A et al 13 (0.89%) whereas slightly higher incidence was seen in other studies 1.3%, 14 1.4%, 15 1.8% 16 and 1.9%. 17 The majority of ectopic pregnancy cases occurred in 30 to 34 years age group (28.4%) which was similar to a study by Kaveri et al, 16 (31 to 35 years). However, other studies [17][18][19] found more of these cases in 20 to 30 years age group.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, more of ectopic pregnancy was seen in multiparous (65%) which is similar to various other studies. 13,16,17,19,20 Amongst the risk factors studied, history of having previous abortion was the most common finding (25%). Similar observations were seen by Rajita et al (28%), 8 Rajendra et al (32.6%) 17 , Shraddha et al (29%), 21 Archana et al (31.2%) 22 and Arati et al (46.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Absence of hemoperitoneum was noticed in 37.2% of patients who were hemodynamically stable in accordance with 22.5%, 24.5% of studies of Shetty KS, Sabina Yeasmin et al The blood loss of less than 500 ml was observed in 13 women (30.23%) comparable to 21.15% of Wakankar et al 19 Hemoperitoneum amounting to 1000 ml or less was noted in 30.2% akin to 36.6% of Kaveri Shaw et al 36 Hemoperitoneum exceeding 500 ml was documented in 15 cases (34.88%) corresponding to 63.46% of cases in study by Wakankar et al 19 Twenty four patients (53.33%) received blood transfusion analogous to 54.8%, 54.9%, of Shetty KS, Pranathi et al 7,22 Multiple blood units (>2) were transfused in 88 % of patients parallel to 57.69% of subjects in studies by Wakankar et al 19 Two patients (4.44%) in shock required inotropic support akin to 11.11% in studies by Dasari U, and 14% each in studies by Shetty VH 18 and Karmakar et al 15 These patients presented late with signs of rupture and hypovolemia. Decompensation with shock is a sign of significant intraperitoneal haemorrhage.…”
Section: Resultssupporting
confidence: 69%
“…Methotrexate was successful in 4.44% of cases akin to 5.5%, 6.14% of Dasari and Sudha VS et al respectively. 14,17 The first successful surgical intervention to treat an ectopic pregnancy was by John Bard, a surgeon in New 5,24 General anaesthesia was administered to 48.88 % corresponding to 38%, 51.92% of Shetty VH, Wakankar et al Nearly 51% of patients were operated under spinal anaesthesia parallel to 46.15%, 62% of Wakankar, Shetty VH et al 18,19 Preponderance of the implantations were in the fallopian tube (95.55%) akin to 94.4%, 94.71%, 96%, 96.2% of S Tahmina, Sudha VS, Singh S, Wakankar et al Ampullary ectopics amounted to 41.86% similar to Porwal S (40%), Mehta A (42.5%), Singh S (44%) et al 9,16,38 Ectopic in isthmus was documented in 9.3% of the patients analogous to 8%, 9.52%, 10.76% of Ganitha, N. Spandana, Chate MT et al 10,13,26 Interstitial ectopic accounted for 9.3% of cases corresponding to 4% each of Mooij and Shetty VH, 6.25% in Kaur N et al 5,18,39 Cornual ectopic (4.65%) was the least common site equivalent to 4.65%, 4.76% of studies by Choudhary, N.Spandana et al 26,40 Non tubal ectopic was seen in two cases (4.65%).Both were pregnancies in rudimentary horn akin to studies by Gaddagi R (9.1%), 4% each of Shalini Kumari and Prasanna B et al 11,12,31 Right sided ectopic cases were paramount accounting to more than 50% of the cases homogenous to studies of Kaveri Patel (50%), Wakankar (55.76%), Sabina Yeasmin (57.44%) et al 19,32,36 About 21 women (46.66%) had left sided lesions comparable to 40%, 42.5% of Shetty VH, Sabina Yeasmin et al 18,32 Nearly 62.79% had hemoperitoneum analogous to 65.3%, 70% of studies by S.Tahmina, Sabina Yeasmin et al…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation